Lorentzian Helicoidsin Three Dimensional Heisenberg Group - Turhan, E.; Altay, G. (Chiang Mai Univ, Fac Science, 2010)
In this paper we study the minimal surface in three dimensional Heisenberg group Heis3. We use Levi-Civita connections and obtain mean curvature of Lorentzian Helicoid. We characterize the Lorentzian Helicoid and obtain the condition of being minimal surface for Lorentzian Helicoid.
Keywords: Heisenberg group; Lorentzian Helicoid; Minimal surface